Problems with Derived Importance Measures in Brand Strategy and Customer Satisfaction Studies - Clancy, Kevin J.; Berger, Paul D.; Krieg, Peter (Indian Journal of Marketing, 2013)
For many years, marketers have studied the determinants of brand choice for products and services. The most common approach has been to ask respondents to "self-report" the importance of many product/service attributes and benefits in a product-category. It later became clear that in many cases, what respondents said was important was not reflected in their brand choices. To help them overcome this weakness, an indirect measurement approach, called Derived- Importance, became a popular way to assess the influence of attributes/benefits on brand-choice or customer-satisfaction. Many of the "statistics" purporting to measure derived-importance have serious problems; these problems are discussed in this paper.